Being and event - Badiou, Alain (Continuum, 2005)
A translation of one of the single most important works of recent French philosophy, Badiou's magnum opus. Being and Event is the greatest work of Alain Badiou, France's most important living philosopher. Long-awaited in translation, Being and Event makes available to an English-speaking readership Badiou's groundbreaking work on set theory - the cornerstone of his whole philosophy. The book makes the scope and aim of Badiou's whole philosophical project clear, enabling full comprehension of Badiou's significance for contemporary philosophy. Badiou draws upon and is fully engaged with the European philosophical tradition from Plato onwards; Being and Event deals with such key figures as Descartes, Spinoza, Leibniz, Hegel, Rousseau, Heidegger and Lacan. This wide-ranging book is organised in a careful, precise and novel manner, reflecting the philosophical rigour of Badiou's thought. Unlike many contemporary Continental philosophers, Badiou - who is also a novelist and dramatist - writes lucidly and cogently, making his work far more accessible and engaging than much philosophy, and actually a pleasure to read. This English language edition includes a new preface, written by Badiou himself, especially for this translation.